Point-of-Care Rapid-Seeding Ventricular Assist Device with Blood-Derived Endothelial Cells to Create a Living Antithrombotic Coating. Issue 4 (July 2016) - Noviani, Maria; Jamiolkowski, Ryan M.; Grenet, Justin E.; Lin, Qiuyu; Carlon, Tim A.; Qi, Le; Jantzen, Alexandra E.; Milano, Carmelo A.; Truskey, George A.; Achneck, Hardean E.
Abstract : The most promising alternatives to heart transplantation are left ventricular assist devices and artificial hearts; however, their use has been limited by thrombotic complications. To reduce these, sintered titanium (Ti) surfaces were developed, but thrombosis still occurs in approximately 7.5% of patients. We have invented a rapid-seeding technology to minimize the risk of thrombosis by rapid endothelialization of sintered Ti with human cord blood-derived endothelial cells (hCB-ECs). Human cord blood-derived endothelial cells were seeded within minutes onto sintered Ti and exposed to thrombosis-prone low fluid flow shear stresses. The hCB-ECs adhered and formed a confluent endothelial monolayer on sintered Ti. The exposure of sintered Ti to 4.4 dynes/cm 2 for 20 hr immediately after rapid seeding resulted in approximately 70% cell adherence. The cell adherence was not significantly increased by additional ex vivo static culture of rapid-seeded sintered Ti before flow exposure. In addition, adherent hCB-ECs remained functional on sintered Ti, as indicated by flow-induced increase in nitric oxide secretion and reduction in platelet adhesion. After 15 day ex vivo static culture, the adherent hCB-ECs remained metabolically active, expressed endothelial cell functional marker thrombomodulin, and reduced platelet adhesion. In conclusion, our results demonstrate the feasibility of rapid-seeding sintered Ti with blood-derived hCB-ECs to generate a living antithrombotic surface. Abstract : Supplemental Digital Content is available in the text.